# How do I do substitution equations

out of the equations in the system, pick the one that has the least amount of funky numbers. then make that equation equal to either x or y(or any other variable dependin on what kind of systems youre doing, usually just x and y in algebra 1). Then plug that equation into the other one and solve.

example:

x+3y=41

2x+2y=15

then change first equation

x=41-3y

plug it in

2(41-3y) +2y=15

simplify and solve

82-6y+2y=15

82-4y=15

82-15=4y

67=4y

67/4=y

then substitute the y value back into one of the equations and you have your answer for x.

P.S. algebra is really annoying...I'm in 9th grade Algebra2/trig....not that hard but really annoying...

## To solve a system of equations using substitution, follow these steps:

1. Identify which equation in the system has the least amount of "funky numbers" (or coefficients that are not easy to work with).

2. Choose that equation and rearrange it so that one variable (let's say x) is isolated on one side of the equation. For example, if you choose the equation x + 3y = 41, you can isolate x by subtracting 3y from both sides: x = 41 - 3y.

3. Substitute the expression for x from the rearranged equation into the other equation(s) in the system. In this example, substitute x = 41 - 3y into the equation 2x + 2y = 15.

4. Simplify and solve the resulting equation for the remaining variable. Continuing with the example, substitute x = 41 - 3y into 2x + 2y = 15: 2(41 - 3y) + 2y = 15. Simplify the equation: 82 - 6y + 2y = 15.

5. Solve the equation obtained in the previous step for y. In this example, 82 - 6y + 2y = 15 simplifies to 82 - 4y = 15.

6. Solve for y: subtract 82 from both sides of the equation to isolate the term with y: 82 - 15 = 4y.

7. Divide both sides of the equation by 4 to solve for y: 67 / 4 = y.

8. Substitute the value of y back into one of the original equations to solve for the other variable, x. Choose either equation, for example, x + 3y = 41: x + 3(67 / 4) = 41.

9. Simplify and solve for x. In this example, x + (3 * 67 / 4) = 41 simplifies to x + 201/4 = 41.

10. Subtract 201/4 from both sides of the equation to isolate x: x = 41 - 201/4.

11. Simplify the equation to get the final answer for x.

Remember to always double-check your solution by substituting the values of x and y back into both original equations to ensure they satisfy both equations simultaneously.